Ecology and DNA Fingerprinting of Cryptocoryne Pallidinervia Engler (Araceae) Accessions Using Polymerase Chain Reaction M13 Universal Primer - Isa, Ipor; WS, Ho; CS, Tawan; MS, Salmizana; M, Noryatimah (Malaysian Society Of Applied Biology, 2007)
The ecological study of Cryptocoryne pallidinervia Engler was conducted at three different locations vis. Sungai Keranji (Lundu), Sungai Batu (Triso, Sri Aman) and Lingga Peat Swamp Forest Reserve (Lingga, Sri Aman). The study comprised of morphological characteristics, growth pattern and biomass allocation of C pallidinervia, forest structure and edaphic conditions of the location of C pallidinervia were carried out. The total dry weight (g/m(2)), plant density, total leaves per m(2), total leaf area (cm(2)/m(2)), leaf area ratio (cm(2)/g), specific leaf area (cm(2)/g), leaf weight ratio (g/g), petiole weight ratio (g/g) and root weight ratio (g/g) varied between localities. Genomic DNA of 18 accessions was amplified with the M13 universal primer (5'- TTATGAAACGACGGCCAGT-3'). A total of 18 distinctive PCR patterns were obtained which composed of 3 to 20 bands with the size ranging from 500bp to 3kb. The PCR profile was further analyzed to establish genetic diversity between through the construction of dendrogram. Cluster analysis of genetic relatedness had divided the C pallidinervia accessions into four different major clusters. All big leaf accessions were grouped together whereas the small leaf accessions can be found in all clusters: Besides that, Bintulu accessions were highly differentiated among the others since they grouped together in different clusters. This indicates that the PCR method with M13 universal primer is a rapid and reliable method to study genetic relatedness of C. pallidinervia accessions from different locations.